«Saharah silk way»’s place in the development of kazakh culture - Зейнолла, Ж; Мың, Нан (Journal of Oriental Studies, 2018)
In history it took its beginning from China, passed through the Central Asia and which is influenced to the growth of international commerce with Europe countries Uly Zhibek Zholy took the especial place in Kazakh culture and in its territory. Itsalso took the central point in connecting Central Asia with other countries. Sahara Silk Road without breaking the culture, clearly demonstrates the ethnography of the Kazakh people in the national colors. Nothing while developing doesnot move in a straight line. As well as the trade «Silk Road» that grows up, then slows down and sometimes it happens that can quite simply be interrupted. In those days, the fierce warrior on the «Silk Road» left a lot of traces of these wars, and later people are once again restored the former order of life. Thus, the second dawn of «Silk Road» took place in the VI-XII centuries AD, which was during the Tang Dynasty. Since Kazakhstan got its independence it is causing its share in developing of Zhibek Zholy. Connecting the past with the present Sahara Silk Road became globally significant in our time, linking and demonstrating on a new Chinese and Kazakh cultures.